2017
DOI: 10.1016/j.jnc.2017.06.002
|View full text |Cite|
|
Sign up to set email alerts
|

Improving landscape connectivity for the Yunnan snub-nosed monkey through cropland reforestation using graph theory

Abstract: , et al.. Improving landscape connectivity for the Yunnan snub-nosed monkey through cropland reforestation using graph theory. Journal for Nature Conservation, Elsevier, 2017Elsevier, , 38, pp.46 -55. 10.1016Elsevier, /j.jnc.2017 Journal for Nature Conservation 38 (2017) 46-55 http://dx.doi.org/10.1016/j.jnc.2017.06.002 Improving landscape connectivity for the Yunnan snub-nosed monkey through cropland reforestation using graph theory Abstract: Habitat fragmentation is a threat to biodiversity because it r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 45 publications
1
28
0
Order By: Relevance
“…Graph theory has become a popular tool for modeling the connectivity between suitable habitat patches (Foltête, Clauzel, & Vuidel, ; Foltête, Clauzel, Vuidel, & Tournant, ). We respectively used the inverse of the habitat suitability map as a resistance surface (Wang et al, ) and identified least‐cost paths (Li, Clauzel, et al, ) to identify the current and future potential habitat corridors for Sichuan golden monkey. All analyses were performed using Graphab 2.2 software (available at https://sourcesup.renater.fr/graphab/en/home.html) (Clauzel, Deng, Wu, Giraudoux, & Li, ).…”
Section: Methodsmentioning
confidence: 99%
“…Graph theory has become a popular tool for modeling the connectivity between suitable habitat patches (Foltête, Clauzel, & Vuidel, ; Foltête, Clauzel, Vuidel, & Tournant, ). We respectively used the inverse of the habitat suitability map as a resistance surface (Wang et al, ) and identified least‐cost paths (Li, Clauzel, et al, ) to identify the current and future potential habitat corridors for Sichuan golden monkey. All analyses were performed using Graphab 2.2 software (available at https://sourcesup.renater.fr/graphab/en/home.html) (Clauzel, Deng, Wu, Giraudoux, & Li, ).…”
Section: Methodsmentioning
confidence: 99%
“…Animals and plants move among different regions of China through dispersal and migration, which support the structure and function of biodiversity and ecosystems. This is particularly important for long-term survival of endangered or rare animal (94) and plant (95) species. Such functional connections are also particularly crucial for the current and future success of protected areas in meeting their conservation goals (96).…”
Section: Flowsmentioning
confidence: 99%
“…With increased fragmentation, the spatial heterogeneity of the landscape becomes more complex and the resistance of different landscapes to the movement of species changes, which affects patterns of migration, dispersal, and gene flow (Laurance et al, 2002;Saunders, Hobbs & Margules, 1991;Zhang & Ma, 2014). Recent studies have tried to characterize the ability of species to move between different patches across the landscape by using cost distance modelling (Howard et al, 2015;Li et al, 2017). Cost distance modelling is a statistical tool designed to estimate the difficulty of a species moving across its distributional range by assigning resistance values for each pixel of a rasterized map and, using a species perspective approach, take into account landscape configuration and physical structure to evaluate landscape connectivity and its effects on the energetics of animal movements (Richard & Armstrong, 2010).…”
Section: Introductionmentioning
confidence: 99%